Esophageal Atresia with Tracheo-Esophageal Fistula Presenting Beyond 7 Days - Nilesh Nagdeve; Mohini Sukhdeve; Tushar Thakre; Suresh Morey (EL-Med-Pub, 2017)
Aim: To describe our experience of neonates with esophageal atresia with tracheo-esophageal fistula (EA with TEF) who presented after a week. Design: Retrospective study of the patients of EA with TEF who presented after a week. Study Setting: Department of Pediatric Surgery, Government Medical College Nagpur. Study Duration: Eight years. Materials and Methods: Demographic information, hematological, biochemical and radiological data were obtained from the patients' medical records. The gap between two ends of the esophagus, nature of upper pouch and lower esophagus were noted intra-operatively. Outcome in terms of mortality and surgical complications were noted. In operated group, babies who survived were compared with non-survivors with respect to various preoperative variables. Results: Of 52 patients, 27 babies expired during initial stabilisation period before surgery. The causes of mortality were severe pneumonitis and septicemia. One baby had associated cyanotic heart disease. Twenty-five patients with mean age of 8.28±1.21 days underwent surgery. Nearly two-third of them were male. All of them were born at full-term with mean birth weight of 2.47±0. 12 kg. More than 80% were previously hospitalised and nearly 70% babies were given feeds before present hospitalization. Mean Downe's score for respiratory distress was 5.8±1.49. All patients were positive for septic profile. Associated congenital anomalies were present in ten patients. Intra-operatively, two ends of esophagus were either approximating or have short gap in 24 patients. All patients had well developed, thick and muscular upper oesophageal pouch. Lower esophagus at fistula was thin but dilated in 18 patients while thin and narrowed in 7 patients. However, esophageal anastomosis was possible with ease without any tension in all except one patient. There were 15 deaths in our study (13 due to pneumonitis and 2 during follow up due to aspiration). Three survivors required anti-reflux surgery. Comparison of preoperative variables of survivors and non-survivors showed a significant difference with respect to the variables like feedings, abdominal girth, immature band cells to neutrophil ratio and nature of pharyngeal or endotracheal aspirate. Conclusions: Late presentations in EA with TEF are associated with high mortality but less anastomotic complications after surgery. Preoperative factors like feedings, abdominal distension, immature band cells to neutrophil ratio and bilious pharyngeal or endotracheal aspirate are associated with high mortality.